Construction and public procurement in Uganda - Emanuele Colonnelli; Nicole Ntungire (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
As it transitions to an oil-producing country, Uganda's investments in infrastructure and physical capital will increasingly depend on the ability of the construction sector to respond to surges in demand and transform investment effort into outcomes. Using administrative and survey data, this paper sets out to examine the current bottlenecks to production faced by the construction sector in Uganda and identifies possible policy remedies to relieve them. A secondary point of emphasis in the paper's analysis is the interaction between government and construction firms through public procurement, and the instrumental role procurement plays in the efficient development of the industry.
Keywords: L74; H57; O13; 330; construction; procurement; natural resources; Uganda